Problems in the reproducibility of classification of small lung adenocarcinoma: an international interobserver study - BOZKURTLAR, EMİNE (My University, 2019)
Aims The 2015 WHO classification for lung adenocarcinoma (ACA) provides criteria for adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (INV), but differentiating these entities can be difficult. As our understanding of prognostic significance increases, inconsistent classification is problematic. This study assesses agreement within an international panel of lung pathologists and identifies factors contributing to inconsistent classification. Methods and results Sixty slides of small lung ACAs were reviewed digitally by six lung pathologists in three rounds, with consensus conferences and examination of elastic stains in round 3. The panel independently reviewed each case to assess final diagnosis, invasive component size and predominant pattern. The kappa value for AIS and MIA versus INV decreased from 0.44 (round 1) to 0.30 and 0.34 (rounds 2 and 3). Interobserver agreement for invasion (AIS versus other) decreased from 0.34 (round 1) to 0.29 and 0.29 (rounds 2 and 3). The range of the measured invasive component in a single case was up to 19.2 mm among observers. Agreement was excellent in tumours with high-grade cytology and fair with low-grade cytology. Conclusions Interobserver agreement in small lung ACAs was fair to moderate, and improved minimally with elastic stains. Poor agreement is primarily attributable to subjectivity in pattern recognition, but high-grade cytology increases agreement. More reliable methods to differentiate histological patterns may be necessary, including refinement of the definitions as well as recognition of other features (such as high-grade cytology) as a formal part of routine assessment.
Keywords: Tıp; Histoloji-Embriyoloji; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Histology and Embryology; Surgery Medicine Sciences; Pathology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; HÜCRE BİYOLOJİSİ; Yaşam Bilimleri (LIFE); PATOLOJİ; Biyoloji ve Biyokimya; CELL BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); PATHOLOGY; BIOLOGY & BIOCHEMISTRY; Patoloji ve Adli Tıp; Histoloji; Biyokimya (tıbbi); Moleküler Biyoloji; Hücre Biyolojisi; Pathology and Forensic Medicine; Histology; Biochemistry (medical); Molecular Biology; Cell Biology; histological pattern; interobserver agreement; lung adenocarcinoma; minimally invasive adenocarcinoma; IASLC/ATS/ERS CLASSIFICATION; PROGNOSTIC-SIGNIFICANCE; INDEPENDENT PREDICTOR; STAGE; ASSOCIATION; CANCER; RECURRENCE; SUBTYPE; MICROPAPILLARY; INVASION; histological pattern; interobserver agreement; lung adenocarcinoma; minimally invasive adenocarcinoma